ANALISA PENGARUH VARIASI TEMPERATUR DAN WAKTU AGING PERLAKUAN PANAS T6 TERHADAP FAKTOR EFETIVITAS REM (FER) DAN KEKERASAN PADA PIRINGAN CAKRAM DARI BAHAN KOMPOSIT ABU DASAR BATU BARA - Seputro, Harjo; Fanani, Ahmad Arif (MEKANIKA: Jurnal Teknik Mesin, 2015)
Be able to change the different characteristics and potential of these results, showing that the Metal Matrix Composite showed an increase in physical and mechanical at any properties. With increasing weight percentage ofparticles in the matrix aluminum metal reinforcement makes a low wear rate against diks manufacture brake.Aluminium composite that bottom ash coal with Mg alloy and SiC factor that could affect the properties of thecomposite, particle distribution amplifier in a metal matrix. From the results of research to get the final hardnesstesting and FER. Effect of aging temperature on the value of FER and violence is in the range of temperature that isvalidated, the higher the aging temperature FER value increases, so does the value of violence. The highest FERvalue for 1.34 reached tepmeratur aging 200 0C and highest hardness value is achieved at temperatures of 180 C.Effect of aging time variation of the value of FER and violence is at varied time spans, the longer aging FER valuethus increased, so did the value of violence. The highest FER value of 1.34 was achieved in a period of 7 hours andachieved the highest hardness value of 7 hoursKata kunci : Aluminium komposit abu dasar batu bara.